THE LEGAL IMPLICATIONS OF THE IMPLEMENTATION OF THE FREE MOVEMENT OF GOODS IN THE EU AND THE SITUATION OF THE ENTREPRENEUR – THE PRODUCER AND THE USER OF MEASURING INSTRUMENTS IN POLAND - Żywicka, Agnieszka (Review of European and Comparative Law, 2020)
The article deals with the situation of entrepreneurs – users and manufactur-ers of measuring instruments in Poland according to the harmonization of the Polish measurement law with the EU law after Polish accession to the European Union . The essence of the free movement of goods is presented as a determinant of technical harmonization of measuring instruments in the Single Internal Market of the EU . The article depicts furthermore the valid legal procedures such as the legal metrological control and the conformity assessment . These procedures are applied to the measuring instruments introduced into the market and being used in the context of the obligations of producers and users of measuring instruments